2018
DOI: 10.1371/journal.pone.0209802
|View full text |Cite
|
Sign up to set email alerts
|

Development of small blood volume assays for the measurement of oxidative stress markers in mammals

Abstract: Measuring oxidative stress has become increasingly valuable in ecological studies, especially when different markers are measured on the same individual. However, many of the current methods lack sensitivity for analysis of low blood volume samples, which represent a challenge for longitudinal field studies of small organisms. Small blood volumes can usually only be analysed by using a single assay, therefore providing limited information on individual’s oxidative profile. In this study, we used blood collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…researchers to perform comprehensive analyses of oxidative stress profile of small wild animals. We present in-house assays optimized to yield the most selective analysis for each marker using the smallest blood volumes possible (Langille et al, 2018).…”
mentioning
confidence: 99%
“…researchers to perform comprehensive analyses of oxidative stress profile of small wild animals. We present in-house assays optimized to yield the most selective analysis for each marker using the smallest blood volumes possible (Langille et al, 2018).…”
mentioning
confidence: 99%
“…Plasma oxidative damage and antioxidant levels were assayed following Langille et al.’s (2018) methods, which are optimised for small blood volumes. We thus only provide a brief overview of these assays.…”
Section: Methodsmentioning
confidence: 99%
“…Total non-enzymatic antioxidant power was assessed with two markers: the ferric reducing/antioxidant power (FRAP) assay and the hypochlorous acid shock capacity (HASC) assay. These markers assay antioxidant power with contrasting mechanisms (see Langille et al, 2018 for details) and comparative studies have found no correlation or a weak positive correlation between them (Costantini, 2011; Vassalle et al, 2004). They are, therefore likely to depict different and complementary pictures of the antioxidant status in sampled individuals (Langille et al, 2018; Vassalle et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations